Effects of recovery beverages on glycogen restoration and endurance exercise performance - Williams, M. B.; Raven, P. B.; Fogt, D. L.; Ivy, J. L. (The Journal of Strength and Conditioning Research, 2003)
The restorative capacities of a high carbohydrate-protein (CHO-PRO) beverage containing electrolytes and a traditional 6% carbohydrate-electrolyte sports beverage (SB) were assessed after glycogen-depleting exercise. Postexercise ingestion of the CHO-PRO beverage, in comparison with the SB, resulted in a 55% greater time to exhaustion during a subsequent exercise bout at 85% maximum oxygen consumption (O2max). The greater recovery after the intake of the CHO-PRO beverage could be because of a greater rate of muscle glycogen storage. Therefore, a second study was designed to investigate the effects of after exercise CHO-PRO and SB supplements on muscle glycogen restoration. Eight endurance-trained cyclists (O2max = 62.1 ± 2.2 ml·kg-1 body wt·min-1) performed 2 trials consisting of a 2-hour glycogen-depletion ride at 65-75% O2max. Carbohydrate-protein (355 ml; 0.8 g carbohydrate (CHO)·kg-1 body wt and 0.2 g protein·kg-1 body wt) or SB (355 ml; 0.3 g CHO·kg-1 body wt) was provided immediately and 2 hours after exercise. Trials were randomized and separated by 7-15 days. Ingestion of the CHO-PRO beverage resulted in a 17% greater plasma glucose response, a 92% greater insulin response, and a 128% greater storage of muscle glycogen (159 ± 18 and 69 ± 32 mol·g-1 dry weight for CHO-PRO and SB, respectively) compared with the SB (p < 0.05). These findings indicate that the rate of recovery is coupled with the rate of muscle glycogen replenishment and suggest that recovery supplements should be consumed to optimize muscle glycogen synthesis as well as fluid replacement.